PENGARUH KOMBINASI TERAPI RELAKSASI PROGRESIF & MUSIK KERONCONG TERHADAP INSOMNIA PADA LANSIA DI POSYANDU SETYA MANUNGGAL III KABUPATEN SEMARANG: THE EFFECT OF COMBINATION OF PROGRESSIVE RELAXATION THERAPY & KERONCONG MUSIC ON INSOMNIA IN THE ELDERLY AT POSYANDU SETYA MANUNGGAL III, SEMARANG REGENCY - Kodir Kodir; Margiyati Margiyati; Tria Friska Ningrum; Dita Amalia (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2020)
Old age is a final stage in the span of human life. Health problems that are often found in the elderly, one of which is psychological disorders, namely anxiety, depression, readiness. These psychological disorders usually cause the emergence of sleep disorders, namely insomnia. Insomnia has an impact on physical effects, namely fatigue and muscle pain. The combination of progressive relaxation techniques and keroncong music is a non-pharmacological therapy given to clients by tensing certain muscles and then relaxing chili sauce accompanied by keroncong music. The purpose of this study was to determine the effect of a combination of progressive relaxation therapy and keroncong music on insomnia in the elderly at the Setya Manunggal III Posyandu, Semarang Regency. This type of research is a quasi-experimental approach with a one group pre-post-test design without control approach. The population of the study was the active elderly who were registered at the Setya Manunggal III Posyandu Lansia as many as 33 elderly. The research sample was determined by purposive sampling by taking into account certain criteria, namely: 1) the elderly who were registered at the Setyamanunggal III Posyandu, 2) aged 60-74 years. 3) Does not experience limitations or paralysis of limbs 4) Likes keroncong music. The exclusion criteria set included: 1) Elderly people with dementia 2) Elderly people who received medication to help sleep/anti-depressants/sedatives 3) Elderly people with total hearing loss. Insomnia measuring instrument using the KSBPJ Questionnaire. The results showed that there was an effect of Combination of Progressive Relaxation Therapy and Keroncong Music on insomnia in the elderly with a t value of 16,142 > t table.